2022
DOI: 10.4254/wjh.v14.i10.1875
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorder and liver injury related to the COVID-19 pandemic

Abstract: Alcohol use disorder is a complex and heterogeneous phenomenon that can be studied from several points of view by focusing on its different components. Alcohol is a hepatotoxin whose metabolism creates profound alterations within the hepatocyte. The liver is the central organ in the metabolism of alcohol, a process that also involves other organs and tissues such as the brain, heart and muscles, but the most relevant organ is the liver. The anatomopathological alterations in the liver associated with the prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…Another fundamental issue is that a potential influence of alcohol use disorder (AUD) on the pattern of liver injury in the case of underlying COVID-19 and possible differences in hepatic manifestation of the disease regarding a previous alcohol abuse history or its absence must be clarified. The inflammatory background of these two conditions appears to be of crucial importance in relation to searching for potential dependencies, even though it can only be speculated which factor is this triggering one: ALD or coronavirus infection [218][219][220]. The data concerning this aspect are rather scarce, nevertheless some attempts to identify the alcoholic background of hepatic complications due to infection with SARS-CoV-2 have already been made.…”
Section: Coronavirus In Ald Patientsmentioning
confidence: 99%
“…Another fundamental issue is that a potential influence of alcohol use disorder (AUD) on the pattern of liver injury in the case of underlying COVID-19 and possible differences in hepatic manifestation of the disease regarding a previous alcohol abuse history or its absence must be clarified. The inflammatory background of these two conditions appears to be of crucial importance in relation to searching for potential dependencies, even though it can only be speculated which factor is this triggering one: ALD or coronavirus infection [218][219][220]. The data concerning this aspect are rather scarce, nevertheless some attempts to identify the alcoholic background of hepatic complications due to infection with SARS-CoV-2 have already been made.…”
Section: Coronavirus In Ald Patientsmentioning
confidence: 99%
“…Other comorbidities straddling between mood and gastrointestinal disorders are those induced by alcohol use, which has markedly increased during the COVID-19 era; social isolation and external stressors have strengthened this correlation [ 81 ]. Alcohol could affect microbiota, while a healthy microbiota could contribute to a regression of liver pathologies, such as steatosis [ 82 ].…”
Section: The Gut Microbiota In Psychiatric Diseasesmentioning
confidence: 99%
“…When considering the death rate of AUD patients before and during the pandemic, the mortality increased by around 20% for both men and women with strongest effects in patients between 25 and 44 years of age (White et al, 2022; Yeo et al, 2022). In addition, numerous studies have reported a reinforced drinking behavior of AUD patients and increased alcohol‐related organ damage in AUD individuals during the pandemic (Hutchison et al, 2022; Kothadia et al, 2022; Marano et al, 2022; Schecke et al, 2022; Tikaria et al, 2022).…”
Section: Epidemiological Studies On Alcohol Consumption and Aud On Co...mentioning
confidence: 99%